Association of single-nucleotide polymorphisms of CDH1 with nonsyndromic cleft lip with or without cleft palate in a northern Chinese Han population. Issue 5 (February 2017) - Song, Hongquan; Wang, Xiaotong; Yan, Jiaqun; Mi, Na; Jiao, Xiaohui; Hao, Yanru; Zhang, Wei; Gao, Yuwei
Abstract: Background: Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is a common congenital malformation among live births, and depends on race and ethnic background. The CDH1 gene plays a vital role in orofacial development. Our research was conducted to examine the association between 3 single-nucleotide polymorphisms in the CDH1 gene and NSCL/P. Methods: Three single-nucleotide polymorphisms (rs16260, rs9929218, and rs1801552) of the CDH1 gene were genotyped using the Snapshot mini-sequencing technique in 331 patients with NSCL/P and 271 controls from the northern Chinese Han population. Results: The investigation indicated that presence of the CDH1 rs1801552 TT genotype under the assumption of a recessive model is related to the decreased risk for NSCL/P (odds ratio 0.53, 95% confidence interval 0.34–0.81, P  = 0.003). The results were still significant after the Bonferroni correction for multiple comparisons. However, nonsignificant differences in rs16260 and rs9929218 were found between cases and controls. Conclusion: Our study demonstrates that the CDH1 polymorphisms were significantly associated with the risk of NSCL/P in the northern Chinese Han population. We provide further evidence regarding the role of CDH1 variations in the development of NSCL/P in a northern Chinese Han population.